Association between Plasma Brain-derived Neurotrophic Factor Level and Alzheimer’s Disease: A Mendelian Randomization Study - You, Jiaxing; Wang, Yinan; Chang, Xinyue; Liu, Yi; He, Yu; Zhou, Xiya; Zou, Jinyan; Xiao, Meng; Shi, Mengyao; Guo, Daoxia; Shen, Ouxi; Zhu, Zhengbao (Current Neurovascular Research, 2023)
Background: High brain-derived neurotrophic factor (BDNF) concentrations have been found to be associated with a decreased risk of Alzheimer’s disease (AD) in observational studies, but the causality for this association remains unclear. Therefore, we aimed to examine the association between genetically determined plasma BDNF levels and AD using a two-sample Mendelian randomization (MR) method. Methods: Twenty single-nucleotide polymorphisms associated with plasma BDNF concentrations were identified as genetic instruments based on a genome-wide association study with 3301 European individuals. Summary-level data on AD were obtained from the International Genomics of Alzheimer's Project, involving 21,982 AD cases and 41,944 controls of European ancestry. To evaluate the relationship between plasma BDNF concentrations and AD, we employed the inverse-variance weighted method along with a series of sensitivity analyses. Results: The inverse-variance weighted MR analysis showed that genetically determined BDNF concentrations were associated with a decreased risk of AD (odds ratio per SD increase, 0.91; 95% confidence interval, 0.86-0.96; p =0.001). The association between plasma BDNF concentrations and AD was further confirmed through sensitivity analyses using different MR methods, and MR-Egger regression suggested no directional pleiotropy for this association. Conclusion: Genetically determined BDNF levels were associated with a decreased risk of AD, suggesting that BDNF was implicated in the development of AD and might be a promising target for the prevention of AD.
Keywords: neuroprotection